Issues of Supplemental Support in Pediatric Ophthalmology - I. A. Gndoyan (Oftalʹmologiâ, 2020)
The ophthalmologist often raises the issues about using of various vitamins, trace elements and other nutrients for the prevention and treatment of the different ocular diseases at their practice. The significance of this problem is caused by the importance of the vision for the socialization of modern person, as well as the high intensity of the visual analyzer using both in the process of performing professional occupation and in the usual indoor/outdoor activities. The issues of the supplemental support in pediatric ophthalmology are especially important, as today formation of the visual organ in children develops under increased visual stress. For the total population, including children, of the industrialized countries the most typical form of vitamin deficiency is subnormal vitamin supply, which occurs among almost healthy children of different ages. The supplemental support issues should be considered in relation to certain types of ocular pathology in children. The most common problem today among children is myopia with projected high increase of this refraction anomaly magnitude in the future. The oxidative stress is the main pathogenesis factor of many degenerative diseases development, including myopia. It is considered as the oxidative stress is realized due to both endogenous processes and various external factors impact, including ultraviolet radiation. Not only vitamins with antioxidant properties (A, C, E), but the trace elements (zinc and copper), bioflavonoids (anthocyanoides) and xanthophilic pigments (lutein, zeaxanthin) are necessary to stabilize myopia and to prevent the development of degenerative diseases in adulthood. These substances are involved in the most important physiological and biosynthetic processes in the sclera, retina and other eye structures and render an influence on its microvessels and hemodynamics in general. All these substances are not synthesized in the human body, and in order to maintain metabolism and homeostasis the sufficient alimentary intake should be provided beginning with early age. The complex drugs, which include multipotential and synergistic active substances, are of particular interest.